THE ATTITUDES OF NCE STUDENTS TOWARDS USE OF INTERNET AT USCOEGA (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
This research work examines the attitudes of Nigerian Certificate in Education (NCE) students towards use of InternetatUmar Sulaiman College of Education Gashua (USCOEGA) in the year 20010/11 academic session. In this connection therefore, the study aims at studying the effect of certain variables such as gender, computer/Internet experiences and Internet perception on learning process at different schools and levels in the college. A survey was carried out with a sample of 240 students from various schools and levels in the USCOEGA. A questionnaire was designed and distributed to the students sample. Surprisingly, the result revealed a limited awareness about the important and the usage of Internet among NCE students and the NCE students learning has no relationship with the usage of Internet. However it was shown that gender has no significant effect towards Internet usage. Furthermore, the study also vindicated that the token amount being paid for the Internet services stops most students from using Internet; in addition to that, contradicted findings were also discovered as a result of falsification of information by some students: conclusively, some list of recommendations were given base on the findings.